Les pancartes méconnues de l’abbaye de Saint-Rigaud (dernier tiers du xie siècle). Transmission, confection, signification - Philippe Lambert (Bulletin du Centre d’Études Médiévales d’Auxerre)
This article presents a first analysis and edition of three little-known documents produced by the abbey of Saint-Rigaud – com. Ligny-en-Brionnais, dep. Saône-et-Loire – during the last third of the 11th century. These documents belong to the diplomatic category of pancartae. They take the form of large sheets of parchment on which at least two deeds were transcribed, the originals of which have not been preserved. An examination of these pancartae from three perspectives – archival conservation, principles of composition and social significance – shows that they are the result of a process of documentary unification involving the selection of scattered texts, rewriting on a new medium and the creation of a thematic discourse. It also shows that their creation at Saint-Rigaud coincided with a pivotal moment for the monastic community, that of its institutional formation and its assertion within the power networks of the Brionnais region.